Sludge Composting: A Case Study on Palm Oil Mill Sludge (POms) - Zahrim, A. Y.; Rakmi, A. R.; Kalil, M. S. (ASEAN Journal of Chemical Engineering, 2007)
Current disposal technology for palm oil mill sludge (POMS) creates problems such as sludge flooding insects, and bad odor mainly during the rain season. This study we present in-vessel composting system as an alternative process for disposal of POMS. Maximum temperature achieved for reactor was about 400C. It can be verified that the composting process followed first order kinetic equation with degradation rate k = 0.014 day-1 with maximum degradation rate of 51%. POMS compost has potential to improve performance of C. citratus growth in sandy soil that usually lacks nutrients and has poor soil structure.